Social Network of the Executive Managers and the Performance of Iranian Start-Up Businesses; Evidence based on the Findings of the Global Entrepreneurship Monitor (GEM) - Moradi Bostanabad , Amir Mohammad (Technium EconomiA, 2024)
Social networks include relationships that provide information and resources needed by entrepreneurs. The aim of the present study is to investigate the effect of using the consulting resources of the social network of entrepreneurs (executive managers) on the performance of Iranian start-up businesses (n=135) that participated in the 2020 research program of the Global Entrepreneurship Monitor. The results of 2020 GEM data based on structural equation modeling show that the size of entrepreneurs' social network has a positive effect on their business performance. Also, the results of the present study indicate that family support of business owners increases the effect of social networks on the performance of their businesses.